Examining “Bossman” Dynamics: Family Communication among Married Women in Nigeria's Predominant Religions - Zacky, Eze Ugochukwu; Judith, Zacky-Eze Chinwendu; Okpoko, Chinwe Cathrine; Ogochukwu, Ogbobe Francisca (International Journal of Qualitative Research, 2024)
Despite advancements in understanding gender roles and family dynamics, significant gaps remain in how these dynamics operate within diverse religious contexts in Nigeria. This study aims to investigate the influence of the 'Bossman' factor, which encompasses diverse gender roles (Breadwinner, Overall decision-maker, Shared power, Supportive husband, Male authority, and Nurturer), on family communication among married women from Christian and Islamic backgrounds. Using a qualitative approach and employing thematic analysis, focus group discussions (FGDs) were conducted with ten married women five Muslims from the central Mosque, Uwani, Enugu State, and five Christians from the Redeemed Christian Church of God (RCCG) Province Five Headquarters, Trans-Ekulu, Enugu State. The findings reveal that the “Bossman” factor significantly influences decision-making processes, particularly in financial matters, and is associated with hierarchical power dynamics. Communication patterns varied from directive to collaborative styles, depending on perceived roles within the “Bossman” factor. Conflicting perceptions among participants highlighted subjective experiences within different gender roles. The study concludes that promoting egalitarian decision-making, facilitating open communication, and challenging traditional gender norms are crucial for fostering healthier family dynamics. These findings contribute to the understanding of gender roles and family communication in diverse cultural and religious settings, offering valuable implications for policymakers, practitioners, and scholars focused on enhancing family well-being.